Pengaruh Model Pembelajaran Berbasis Masalah dan Regulasi Diri Terhadap Hasil Belajar PKn Kelas V di MI Muhammadiyah Kabupaten Sidoarjo: The Influence of Problem-Based Learning Models and Self-Regulation on Learning Outcomes of Civics Class V at MI Muhammadiyah Sidoarjo Regency - Fihayati, Zuyyina (Universitas Muhammadiyah Sidoarjo, 2018)
The role of students is needed to improve student learning outcomes, in this case the students are expected to be able to manage or manage himself. This study aims to prove the difference between problem-based learning model and lecture learning. In addition, it also proves that the use of Problem-Based learning model and lecture learning in children who have high regulation and children who have low regulation of the results of learning Civics and to prove the interaction of the implementation of Learning and self-regulation affect the results of learning Civics class V in MI Muhammadiyah district Sidoarjo. The results of this study indicate 1. There are differences in the results of learning PKN class V by using Problem-Based Learning Model with the use of Lecture Learning in MI MuhammadiyahSidoarjo district; 2. There are differences in the results of Civics learning in grade V children who have high self-regulation and children who have low regulation; 3. There is an interaction of the application of learning and Self Regulation has an effect on the learning result of VII C grade in MI Muhammadiyah of Sidoarjo Regency.